QUALITY INDICATORS AND THEIR APPLICATION (Scientific journal of the Fergana State University, 2024)
The article analyzes indicators that determine and show the quality of the world's soils, their types, and their relationships with soil function. The article shows soil quality indicators that are used at a high level in the USA, Sweden, New Zealand, Australia, China, The Netherlands, Canada, Great Britain, Italy, Columbia, France, and other countries, and also highlights problems in the development and use of soil quality indicators in soil science of Uzbekistan.